Hill Cipher Cryptosystem over Complex Numbers - Maxrizal Maxrizal (Indonesian Journal of Mathematics Education, 2019)
The Hill Cipher cryptosystem is a symmetry key cryptosystem. This cryptosystem uses the concept of integer over modulo p. This cryptosystem uses a matrix K as a secret key. We must choose the key matrix K which has an inverse in modulo p. This secret key matrix will be used by the sender and recipient of the message to encrypt and descript the message. For this reason, this paper will discuss the generalization of Hill Cipher using matrices over complex numbers. Calculation of determinants and inverses of the matrix K will adopt a system of determinant and inverse calculations on Hill Cipher. The results show that the proposed cryptosystem scrambles the plaintext.